WHO CAN SAFELY SKIP SURGERY? PREDICTORS OF SUCCESS AND FAILURE OF NONOPERATIVE MANAGEMENT IN ACUTE UNCOMPLICATED APPENDICITIS - Grzelak, Oliwia; Kuśmierczyk, Weronika; Bolek, Oliwia; Sordyl, Katarzyna; Szczepański, Piotr; Rogulski, Krzysztof; Majkowska, Magdalena; Fengier, Maria; Kącikowska, Justyna; Trzaskowski, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and objective: Acute appendicitis is one of the most common surgical emergencies worldwide. Although appendectomy remains the standard treatment, nonoperative management (NOM) with antibiotics has emerged as an alternative for selected patients with acute uncomplicated appendicitis. While randomized trials have confirmed the safety and noninferiority of NOM, treatment failure and recurrence remain important limitations. This review aims to summarize current evidence on predictors of success and failure of NOM in acute uncomplicated appendicitis. Methods: A comprehensive literature search was performed in PubMed, Embase, Google Scholar, and Web of Science for studies published between January 2000 and January 2025. Randomized controlled trials, observational studies, systematic reviews and meta-analyses evaluating predictors of NOM outcomes were included. Due to heterogeneity among studies, results were synthesized narratively. Results: Sixteen studies comprising 6,281 patients treated with NOM were analyzed. Overall, NOM demonstrated noninferiority to surgical treatment in selected patients; however, approximately 24% required subsequent appendectomy. The presence of an appendicolith was the most consistent predictor of NOM failure and recurrence. Increased appendiceal diameter, elevated C-reactive protein levels, fever, and imaging features suggestive of advanced inflammation were also associated with poorer outcomes. Demographic factors such as age and sex showed inconsistent associations. Conclusions: Nonoperative management with antibiotics is a safe and effective option for carefully selected patients with acute uncomplicated appendicitis. The presence of an appendicolith, appendiceal diameter greater than 10mm and elevated inflammatory markers are key predictors of NOM failure and should be incorporated into clinical decision-making.